THE EFFECTIVENESS OF PEER GROUP EDUCATION TOWARD ADOLESCENTS’ KNOWLEDGE LEVEL OF SEXUAL EDUCATION IN TUMPAK REGION MOJOKERTO - Prasastia Lukita Dewi, Catur; Wahyu Kristiani, Septi (JURNAL KEPERAWATAN SEHAT, 2015)
The sexual issue of adolescents turns out to be a health problem in which it is necessary to get a serious attention since it deals with some aspects within life and human development. Adolescents will imitate and follow what their friends do for reasons to try as well as solidarity as friend without considering the consequences itself. Nowadays, adolescents’ delinquencyis spreading out and often happening in surrounding societies. This study aimed at investigating the effectiveness of peer group education toward adolescents’ knowledge level of sexual education. This study used experimental research design with the approach of One-Group Pre-Post Test Design. The number of population were 85 respondents and the number of sample were 56 respondents in which taken by using stratified sampling. The data were collected by using questionnaires. The Wilcoxon test result shown that the value of Zcalculation-6,886 >Ztableand the significant value was 0,000 < α: 0,05. It means that H1was accepted and Ho was rejected, so that peer group education was really to increase adolescents’ knowledge level of sexual education in Tumpak Region Sidoharjo Village GedegSud-District Mojokerto Regency.This happened because of the knowledge were acquired from accurate source through educational processes regarding giving workshop which was done by the same age-level friends. Therefore, the materials itself were able to be received and comprehended as well. In order to increase adolescents’ knowledge level of sexual education, the processes are better to be done by the same age-level friends to get the information about sexual education properly.Key words: Adolescents, Peer Education, Sexual Education